PERSEPSI MASYARAKAT TERHADAP PERAN ULAMA SEBAGAI OPINION LEADER DI DESA BABELAN KOTA, KABUPATEN BEKASI - Wardi, Miftahussa'adah; Latifah, Farah Nur (An-Nida : Jurnal Komunikasi Islam, 2024)
Ulamas have a huge role in people's lives. Many consider the presence of Ulama as knowledgeable people, religious teachers, and advice givers. So that whatever is said, will be heard and followed by the community because it is considered correct. This unwittingly makes the Ulama an opinion leader in the community. The existence of opinion leaders is one of the elements that influence the flow of communication, especially in rural areas. Various changes and progress in society are determined by the role of opinion leaders. The ulama are the driving force in increasing the high enthusiasm of the village community in carrying out activities, especially religious activities. The purpose of this research is to find out how big the role of ulama in spreading the teachings of Islam in rural areas and what kind of influence is felt because of the presence of these ulama in the community. The method used is using qualitative method.